Condiç\~ao alimentar e distorç\~ao idade-série escolar no Brasil: Análise dos efeitos com modelos de tratamento binários e multivalorados para 2023 - Juliane da Silva Ciríaco; Sandro Pereira Silva; Otoniel Rodrigues dos Anjos Júnior; Julyan Gleyvison Machado Gouveia Lins; Cinthia Barbosa Sousa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This study aims to analyze the impact of food and nutrition insecurity (IAN) on the agegrade distortion of Brazilian students enrolled in the basic education system, based on the database of the special supplement of the Continuous National Household Sample Survey (PNAD Contínua) of 2023. To achieve this objective, matching techniques, such as PSM, and reweighting methods, such as inverse probability weighting (IPW) and weighting with regression adjustment (IPWRA), were used. Subsequently, a multivalued treatment approach was adopted to measure differently the effects of different levels of IAN on school delay. The results show that severe IAN has an impact on students of both sexes, for urban and rural areas of the country. Specifically, the impacts are more pronounced for female students in urban areas (6.9 percentage points) compared to those in rural areas (6.2 p.p.). Furthermore, for male students, the impact is also relevant, with the impact being greater in rural areas (5.9 p.p.) compared to urban areas (5.5 p.p.). These findings highlight the importance of public policies that are sensitive to gender and territorial inequalities, since the effects of IAN on education vary according to the context analyzed, with a higher impact among the most socioeconomically vulnerable population.
Keywords: I14; I31; Q18; R22; 330; food and nutritional insecurity; basic education; age-grade distortion; social determinants; public policy subsidies